International Health Regulations in practice: Focus on yellow fever and poliomyelitis. Issue 10 (2nd October 2016) - Simons, H.; Patel, D.
ASBTRACT: The spread of infectious disease represents a global threat and therefore remains a priority on the international public health agenda. The International Health Regulations (IHR) (2005) came into effect in June 2007 and provide a legal framework to which the 196 member states of the World Health Assembly agree to abide. 1 These regulations include implementation of protective, control and response measures at points of entry to a country (i.e. land borders, sea and airports), and of notification measures, all of which aim to prevent or limit the spread of disease while minimising disruption to international trade. The World Health Organization can apply and enforce IHR (2005) to any disease considered to pose a significant threat to international public health. This short paper focuses on 2 diseases; yellow fever and poliomyelitis, both of which have the potential to spread internationally. It will discuss the measures applied under IHR (2005) to minimize the threat, and explore the implications for both travelers and travel health advisors.